PENINGKATAN KOMPETENSI BISNIS SISWA MAN 4 BANTUL YOGYAKARTA PADA PEMASARAN DIGITAL DENGAN BUSINESS MODEL CANVAS (BMC) - Amri Amrullah, Yusuf; Purwanto, Muhamad Idris; Fauzi, Moch Farid (LPPM Universitas Bina Bangsa, 2025)
The digital era has entered various activities in daily life, without exception in the field of business. Many people run a business by themselves, nowadays business learning has entered the academic realm, from kindergarten to college level education. MAN 4 bantul has concentrated on increasing studin entrepreneurship, one from of support in entrepreneurship subjects, providing facilities for students who take part in competitions and practice selling every year from the results of student business ideas. However, this needs to be improved, so the role of universities in helping to improve entrepreneurial activities at MAN 4 Bantul is one of them through lecturer community service. The output of this activity is introducing digital and online business to students as part of business upgrading efforts using Business Model Canvas (BMCC), so that it will increase the reach of the business run